Genotype of Brahman and Brahman Cross Cattle based on SNP in Insulin-Like Growth Factor Binding Protein-3 (IGFBP-3) gene sequences - DWI AHMAD PRIYADI; PANJONO PANJONO; SIGIT BINTARA; TETY HARTATIK (Society for Indonesian Biodiversity, 2017)
Priyadi DA, Panjono, Bintara S, Hartatik T. 2017. The genotype of Brahman and Brahman Cross Cattle based on SNP in Insulin-Like Growth Factor Binding Protein-3 (IGFBP-3) gene sequences. Biodiversitas 18: 795-800. The IGFBP-3 gene is a potential marker of cattle growth, which is related to the functions that influence the growth, energy metabolism, reproduction and immunity. The genome was isolated from whole blood samples of 10 Brahman cattle and 16 Brahman Cross cattle. Cattle IGFBP-3 gene that targeted in this study was located in the part of intron 2, exon 3 and part of intron 3. The gene targets were amplified using specific primers by Polymerase Chain Reaction (PCR) technique, resulting 563 bp amplification product. As data comparison to reveal the SNP, the GenBank sequences (n = 14) from various breed and countries were used. The objective of this study was to reveal the SNP on the Brahman and Brahman Cross IGFBP-3 gene. The results obtained 3 genotypes from one SNP that spread in the sample population. The SNP was located in intron 2 at position 3,930 (Gïƒ A). The Polymorphism could be recognized by PvuII restriction enzymes. There was not enough evidence to associate the SNP with the phenotype (at pre-weaning age) of Brahman and Brahman Cross cattle. There was a genetic diversity in the population studied. Knowledgeable SNP could be used as genetic markers for further research on Brahman and Brahman Cross cattle.